Effect of water/glycerol polymorphism on dynamic nuclear polarization. Issue 15 (5th April 2018) - Leavesley, Alisa; Wilson, Christopher B.; Sherwin, Mark; Han, Songi
Abstract : The propensity of water/glycerol glasses to form polymorphs influences the performance and reproducibility of dynamic nuclear polarization amplification of NMR signal. Abstract : A paramount feature of robust experimental methods is acquiring consistent data. However, in dynamic nuclear polarization (DNP), it has been observed that the DNP-induced NMR signal enhancement of nominally the same sample can vary between different experimental sessions. We investigated the impact of various freezing conditions on the DNP results for a standard sample, a 50/40/10 by volume d8 -glycerol/D2 O/H2 O solution of 40 mM 4-amino TEMPO, and found that annealing the samples 10 K above the glass transition temperature ( T g ) causes significant changes to the DNP profiles and enhancements compared to that in rapidly frozen samples. When varying the glycerol composition to yield a solution of 60/30/10 d8 -glycerol/D2 O/H2 O, the DNP performance became markedly more consistent, even for samples prepared under vastly different sample freezing methods, in stark contrast with that of the 50/40/10 solution. The EPR lineshapes, T m, and glass transition temperature, T g, were measured under the same sample and experimental conditions as used for the DNP experiments to support the conclusion that different freezing methods change the distribution of 4-amino TEMPO radials in the 50/40/10 solution due to the formation of different polymorphs of the glass, which is mitigated in the 60/30/10 solution and is consistent with the water/glycerol vitrification literature.